EDUCATION AND CHALLENGES OF CONTEMPORANEITY (REMARKS ON THE RESEARCH PROJECT) - D. YU. Korol' (Moscow Polytechnic University, 2016)
The article analyzes how the traditional educational practices cooperate with rapidly changing socioHcultural and technological landscapes. It traces the appearance, the nature and the development of new educational situations in higher education. The article focuses on the impact of the digital informational environment on the discursive environment of education, which results in what has been expressed by a metaphor of "disruption" of contemporary educational space.